Superderivations for a Family of Lie Superalgebras of Special Type (Communications in Mathematical Research, 2021)
By means of generators, superderivations are completely determined fora family of Lie superalgebras of Special type, the tensor products of the exterioralgebras and the finite-dimensional Special Lie algebras over a field of characteristic $p > 3$. In particular, the structure of the outer superderivation algebra is concretelyformulated and the dimension of the first cohomology group is given.
Keywords: divided power algebra; special algebra; superderivation.